Cowboys - Murdoch, David Hamilton, 1937-; Brightling, Geoff (Madrid : Altea, 1994)
Text and photographs trace the history and lore of cowboys around the globe.
Translation of: Cowboy.
"A Dorling Kindersley book"--T.p. verso.
Includes index.
Keywords: Cowboys -- West (U.S.) -- Juvenile literature; Cowboys -- Juvenile literature